Research on hardware-in-the-loop simulation of single point suspension system based on fuzzy PID. (24th April 2020) - Yang, Jie; Gao, Tao; Yuan, Shengli; Shi, Heng; Zhang, Zhenli
The stability control of maglev trains is one of the core problems in the research of maglev train technology and the realisation of this goal is of the great scientific value in the field of magnetic levitation. Based on this, the research on the suspension control strategy of single point maglev system is founded and the control strategy is verified by experiments on Magnetic Levitation Ball System (MLBS). Aiming at the structure of multi-group independent control system of maglev train suspension frame, in order to improve the overall stability control ability of the suspension frame, the coupling relationship between the subsystems is established by introducing the suspension response deviation compensator. Finally, the effect of single point suspension control system is discussed and the cooperative control of suspension frame is carried out on MATLAB. Simulation and analysis show that each subsystem has good anti-jamming ability and the suspension system realises the balanced and stable control under different interference signals, which provides a certain reference value for further study of maglev train suspension control.